Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Enhancing flame retardancy and mechanical properties of epoxy/carbon fiber composites via a metal-phosphorus synergistic interface structure - Dou Hu; Guo-rui Zhang; Xiao-dong Qi; Jing-hui Yang; De-xiang Sun; Yong Wang (Chemical Engineering Journal, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Senescent endothelial cells: a potential target for diabetic retinopathy - Ying-Lu Liao; Yi-Fan Fang; Jia-Xing Sun; Guo-Rui Dou (Angiogenesis, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Shear wave velocity inversion based on Scholte waves for a fully saturated seabed - Xingye Sun; Zhen Guo; Shengjie Rui; Yuzhe Dou (Soil Dynamics and Earthquake Engineering, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

The influence of ADAR1’s regulation on lymphocyte cell function during rejection - Lei Cai; Yan Li; Feng Liu; Wei Zhang; Binliang Huo; Wei Zheng; Rui Ding; Jiyuan Guo; Qingchuan Zhao; Kefeng Dou (Molecular Biology Reports, 2010)